Effectiveness of PrEP (Pre-Exposure Prophylaxis) Integrated into Venereology Services : A Systematic Review - Jerymia Bangun; Wynna Manami; Zahra Astriantani Sulih (International Medical Journal Corp. Ltd, 2026)
Background: Pre-exposure prophylaxis (PrEP) is highly effective for HIV prevention, but optimal service delivery models remain unclear. Integrating PrEP into venereology and sexual health services offers a promising approach to reach at-risk populations, yet real-world effectiveness, uptake, retention, and implementation outcomes vary substantially across settings. Methods: This systematic review synthesized 80 studies examining PrEP integration into venereology, sexual health, and STI clinics across North America, Europe, sub-Saharan Africa, Latin America, and Asia-Pacific. We included randomized controlled trials, cohort studies, demonstration projects, and implementation research reporting outcomes on PrEP uptake, adherence, retention, HIV incidence, STI outcomes, and service delivery innovations. Results: Integrated PrEP services demonstrated high HIV prevention effectiveness, with incidence rates ranging from 0.13 to 0.24 per 100 person-years and risk reductions of 86–90% in large trials (1,3,14). However, uptake varied substantially: 57.1% in England (1), 14.9% among US women (6), 40.6% in Kenyan family planning clinics (12), and 98.1% in a Paris hospital (13). Retention declined steeply over time, from 57% at 1 month to 23% at 12 months in Kenyan public clinics (14,15), but reached 85.9% at 12 months in a Thai community program (16). Self-reported adherence significantly overestimated biomarker-confirmed adherence, especially among people who inject drugs (77% vs 3% with protective levels) (57). STI incidence was high (68.1/100 person-years in England) but concentrated in a minority of users (24% accounted for 79.5% of diagnoses) (1). Telehealth, peer navigation, and dynamic choice models improved outcomes. Long-acting injectable PrEP showed 60.9% full adherence in early implementation (66). Discussion: Integration effectiveness depends critically on population-specific barriers, implementation support intensity, and retention strategies. Settings with comprehensive support (monthly counseling, SMS reminders, community delivery) achieved far better retention than basic integration into existing infrastructure. Self-reported adherence is unreliable, particularly in marginalized populations. STI increases often reflect intensified surveillance rather than true risk compensation. Conclusion: Integrating PrEP into venereology services is effective and feasible, but success requires tailored, multi-component implementation strategies. Retention, not just initiation, is the critical intervention target. Biomarker-validated adherence monitoring and enhanced support for younger, socioeconomically deprived users are essential.